FAMILY REPRESENTATION IN ALI DAN RATU-RATU QUEENS MOVIE - Moh Mahrush Ali; Kamila Nida’unnada; Nuriyah Sa’adah (LPPMPP Institut Seni Indonesia Padangpanjang, 2022)
This study explains the representation of family values in the film